Formulation Development and In Vitro Evaluation of Effervescent Floating Matrix Tablets of Rosuvastatin Calcium - K. Ashok; M. Kishore Babu; N.V.N. Prasanna; B. Venkata Padmavathi; A. Ranga Bhavani; CH. Kalyani; A. Anjali (International Journal of Pharmacy and Analytical Research, 2026)
The present study aimed to develop effervescent floating matrix tablets of Rosuvastatin calcium using direct compression with sodium bicarbonate as a gas-generating agent and polymers including HPMC K100M, Carbopol 934P, guar gum, and xanthan gum. Tablets were evaluated for pre-compression parameters, physical properties, buoyancy, and in vitro drug release. Optimization was performed by varying polymer type and concentration. FT-IR analysis confirmed no significant drug–excipient interactions. The optimized formulation (F10) showed sustained drug release up to 24 h (99.65% cumulative release) with a floating time exceeding10 h. Drug release followed the Higuchi model (R² = 0.996) and exhibited a non-Fickian diffusion mechanism.